Sensory descriptive and comprehensive GC-MS as suitable tools to characterize the effects of alternative winemaking procedures on wine aroma. Part I: BRS Carmem and BRS Violeta - Machado de Castilhos, Mauricio Bonatto (2019)
This study analyzed the volatile composition and aroma profile of BRS Carmem and BRS Violeta red wines elaborated from traditional and two alternative winemaking procedures: grape pre-drying and submerged cap. The wines contained higher concentration of acetates (ranging from 303 mg L-1 to 905 mg L-1) and ethyl and methyl esters (ranging from 138 mg L-1 to 415 mg L-1). The BRS Carmem wines were described as fruity due to the higher concentration of esters and BRS Violeta wines were described as vegetal mainly due to the higher concentration of terpenes and methoxyphenols. C6 alcohols also influenced the vegetal notes of BRS Violeta wines from traditional and submerged cap procedures and the pre-dried wines also presented a relevant jam note possibly due to the presence of 2-phenylethyl acetate. The changes in winemaking procedures can possibly lead to changes in the aromatic profile of red wines in a positive way, improving the wine aroma quality.